Difficulty in implementing a family intervention for bipolar disorder: the predictive role of patient and family attributes. - Tompson, M; Rea, M; Goldstein, M; Miklowitz, D; Weisman, A (2000)
Family affect was examined as a predictor of difficulty implementing a 9-month, manual-based, psychoeducational family therapy for recently manic bipolar patients. Prior to therapy, family members were administered measures to assess both their expressed emotion and affective behavior during a family interaction task. Following family treatment, both therapists and independent observers rated the overall difficulty of treating the family, and therapists also rated each participant's problem behaviors during treatment, in the areas of affect, communication, and resistance. Therapists regarded affective problems among relatives and resistance among patients as central in determining the overall difficulty of treating the family. Relatives' critical behavior toward patients during the pretreatment interaction task predicted both independent observers' ratings of overall treatment difficulty and therapists' perceptions of relatives' affective problems during treatment. Moreover, patients' residual symptoms predicted independent observers' ratings of overall difficulty and therapists' perceptions of patients' resistance to the family intervention. Results suggest that difficulties in conducting a manual-based family intervention can be predicted from systematic, pretreatment family and clinical assessment.